EVALUATION OF THE ALLERGEN IMMUNOTHERAPY EFFICIENCY IN CHILDREN WITH BRONCHIAL SEASONAL ASTHMA USING DOPPLER EXAMINATION OF THE MAJOR SALIVARY GLANDS AND THYROID GLAND - M. V. Ryazanov; L. S. Namazova-Baranova; A. G. Nadtochy (Педиатрическая фармакология)
The article is devoted to the potentialities of ultrasound diagnostics as an additional criterion for the effectiveness of various methods of introducing allergens in children with seasonal asthma in remission during allergen immunotherapy (AIT). For the first time the dynamics of parenchymal blood flow to the salivary glands of the background of the allergen immunotherapy has been evaluated. It was established that during AIT the significant activation of parenchymal blood flow was noted. It is shown that the pathogenetically substantiated therapy leads to improvement of the child state, which echographically was demonstrated by the normalization of hemo dynamic intraorganic vessels.